Business Transportation Policy in Indonesia within the Framework of Social Justice in the Digital Era - Faizin, Moh; Setiady, Tri; Sembiring , Adil; Armeta, Zhelin (Indonesian Journal of Law and Economics Review, 2026)
General Background: The rapid expansion of online transportation in Indonesia has transformed the transportation business landscape in the digital era, creating regulatory coexistence between conventional and application-based services. Specific Background: Despite the issuance of Ministerial Regulations governing non-route passenger transport and special rental transport, disparities persist between conventional transportation and online transportation regarding licensing, vehicle standardization, company status, and driver employment relationships. Knowledge Gap: Previous legal studies have discussed consumer protection, driver responsibility, and policy dynamics, yet none have examined Indonesian transportation business policy comprehensively through the framework of John Rawls’ theory of justice, particularly concerning distributive justice and legal equality between online and conventional sectors. Aims: This study analyzes Indonesian transportation policy within a justice-based framework by comparing regulatory structures for conventional and online transport and evaluating them using Rawls’ principles of justice as fairness. Results: The findings reveal structural legal inequality, including differences in driving licence requirements, unequal regulatory burdens, and the classification of application companies as technology firms rather than transportation companies, resulting in limited legal protection for online drivers. Comparative analysis with Singapore and Malaysia demonstrates more balanced regulatory models. Novelty: This research offers a normative juridical evaluation of transportation regulation grounded explicitly in Rawlsian justice theory, linking licensing disparity and company status to principles of equal basic liberties and the difference principle. Implications: Policy reconstruction through the forthcoming Online Transportation Bill is necessary to harmonize licensing, clarify corporate legal status, and secure equitable legal protection for drivers within Indonesia’s rule of law framework. Highlights: Regulatory asymmetry exists between conventional operators and application-based services in licensing and operational standards. Technology-company classification limits corporate obligations toward drivers within the gig-based partnership model. Comparative ASEAN frameworks demonstrate more balanced governance structures for point-to-point transport services. Keywords: Justice as Fairness, Online Transportation, Legal Equality.